(untitled) (Bangladesh Journal of Medical Science, 2026)
Integration of teaching in medical education is increasingly used to reduce isolation of disciplines and make learning more clinically meaningful across the entire medical program. Integration refers to program-level design of curriculum that purposefully connects basic sciences, clinical sciences, population health, ethics and professionalism across the spectrum of teaching and assessment. Two core approaches of integrations are horizontal integration which links disciplines within the same phase and vertical integration which links foundational and clinical learning across the course. Potential benefits include stronger perceived relevance, improved coherence of learning, earlier development of clinical reasoning, and better preparedness for clinical work when integration is aligned with active learning and assessment strategies. Implementation requires careful curriculum mapping with blueprinting, faculty development, interdepartmental coordination, and assessment redesigned to avoid overload and unintended stressors. BJMS, Vol. 25 No. 02 April’26 Page: 467-472